DOI: 10.1016/s0278-0984(06)14001-8
|View full text |Cite
|
Sign up to set email alerts
|

Tinkering Toward Accolades: School Gaming under a Performance Accountability System

Abstract: We explore the extent to which schools manipulate the composition of students in the test-taking pool in order to maximize ratings under Texas' accountability system in the 1990s. We first derive predictions from a static model of administrators' incentives given the structure of the ratings criteria, and then test these predictions by comparing differential changes in exemption rates across student subgroups within campuses and across campuses and regimes. Our analyses uncover evidence of a moderate degree of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
97
0

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 138 publications
(98 citation statements)
references
References 16 publications
1
97
0
Order By: Relevance
“…Research on quality disclosure in education often focuses on accountability or the supply side-how schools respond to the disclosure of information about the schools. Examples include Carnoy and Loeb (2002), Hanushek and Raymond (2004), Jacob (2005), Peterson and West (2003), Haney (2000), Cullen and Reback (2006), and Figlio and Getzler (2006). 4.…”
Section: Introductionmentioning
confidence: 99%
“…Research on quality disclosure in education often focuses on accountability or the supply side-how schools respond to the disclosure of information about the schools. Examples include Carnoy and Loeb (2002), Hanushek and Raymond (2004), Jacob (2005), Peterson and West (2003), Haney (2000), Cullen and Reback (2006), and Figlio and Getzler (2006). 4.…”
Section: Introductionmentioning
confidence: 99%
“…These studies address the concern that teaching to the test artificially inflates test scores following the introduction of high-stakes testing. See Cullen and Reback (2006) for an assessment of strategic efforts among Texas schools to improve reported scores by manipulating which students are exempt from testing. Jacob and Levitt (2003) provide evidence that some teachers or principals in Chicago actually changed student answers after highstakes assessments in the 1990s.…”
Section: Introductionmentioning
confidence: 99%
“…Previous work has demonstrated that schools often respond strategically to the implementation of a performance measurement system (e.g., Cullen & Reback, 2006;Figlio & Getzler, 2002; Jacob, 2005;Jacob & Levitt, 2003). One strategy that MPCP schools could potentially employ in response to the new high-stakes testing policy could involve manipulation of the pool of lowperforming students who must take the WKCE.…”
Section: "Intent To Treat" and Representative Mps Comparisonsmentioning
confidence: 99%